PROMOSI EVENT OTOMOTIF KAPACAK OPEN DRAG RACE DI PADANG MELALUI MEDIA POSTER - Rizki Afdali, Drs.Syafwan, M.Sn, Ishakawi, S. Pd, M. Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Kapacak is a company in the form of CV. Engaged in the Event Organizer / EO, CV. Kapacak established in 2011, is often organized sports automotive drag race, drag race is a race car on two different tracks and adjacent to, the time gauge in determining the winner. In any event the implementation of the drag race, CV. Kapacak never use the sponsor, although the sponsor's promotion is done better and more interesting than that in doing CV. Kapacak own. Therefore CV. Kapacak want to create a new media campaign, such as posters. In designing a poster using SWOT theory study, then support with AIDAS theory and USP. Keywords: Kapacak, events, promos, Poster